Nurse Adaptability and Post-traumatic Stress Disorder Symptoms During the COVID-19 Pandemic: The Effects of Family and Perceived Organizational Support - Cockerham, Mona; Beier, Margaret E.; Branson, Sandy; Boss, Lisa (Frontiers in Psychology, 2022)
Objective: To examine the effect of family and perceived organizational support on the relationship between nurse adaptability and their experience with COVID-related PTSD symptoms in frontline nurses working on COVID 19 units. Background: Proximity to and survival of life-threatening events contribute to a diagnosis of PTSD, which is characterized by avoidance of reminders of trauma, intrusive thoughts, flashbacks of events, sleep disturbances, and hypervigilance. Using the job-demands and resource model, we examined the effect of adaptability, family support, and perceived organizational support on PTSD symptoms for nurses during the COVID-19 pandemic. Specifically, we tested whether perceptions of environmental supports – i.e., family and organizational support – moderated the relationship between nurse adaptability and COVID-related PTSD symptoms. Methods: A sample of frontline nurses working on COVID 19 units during the COVID-19 pandemic in Texas (N=277) participated in this cross-sectional, observational study. Frontline Nurses reported demographic information and completed surveys designed to measure adaptability, perceived organizational support, family support, and COVID-related PTSD symptoms. Results: Adaptability was significantly positively correlated (medium effects) to perceived organizational and family support (r = .51 and .56 respectively, p < .01). Adaptability and perceived organizational support were also negatively correlated with COVID-related PTSD symptoms (medium effects). Adaptability was negatively correlated with COVID-related PTSD symptoms, supporting Hypothesis 1 (r = -.43, p < .01). Perceived organizational support was also significantly negatively correlated with COVID 19-related PTSD symptoms (r = -.30, p < .01). Family support was not significantly correlated with COVID-related PTSD but was positively related to experiencing COVID-related PTSD after other variables were accounted for. Conclusion: Findings suggest that individual adaptability and organizational support may reduce PTSD severity in frontline nurses working during a crisis; however, family support may increase PTSD symptoms. We provide suggestions for strengthening individual adaptability and healthcare leadership including remaining highly engaged to show support by providing rapid communication, remaining calm during difficult circumstances, maintaining a consistent, physical presence during difficult times. Moreover, our results suggest additional support for nurses with families to adapt to crisis.